The Vanished Settlers of Greenland In Search of a Legend and Its Legacy - Rix, Robert W. (Cambridge Cambridge University Press, 2023)
Introduction; Prologue: The Medieval Settlements in Greenland; 1. Land of Wealth and Violence: Early Representations of Greenland; 2. Greenland and Discourses of Possession; 3. Beyond the Horizon: Greenland in Eighteenth-Century Perspectives; 4. 1818: British Greenland; 5. Greenland's Fall and Restoration; 6. The Surpassing Adventures of Allan Gordon; 7. Arctic Adventure Tales: Science and Imperialism; 8. Vanished Settlers: A Return to New Beginnings; Conclusion.
E-Book / Zugriff nur im Lesesaal